Communication strategies to counter stigma and improve mental health and substance use disorder policy - McGinty, Emma (Psychiatr Serv, 2017)
Despite high burden and poor rates of treatment, public support for allocating resources to improving mental illness and substance use disorder treatment is low. A growing body of research suggests that effective policy communication strategies can increase public support for policies benefitting people with these conditions. In October 2015, the Center for Mental Health and Addiction Policy Research at Johns Hopkins University convened an expert forum with the goals of identifying what is currently known about the effectiveness of such policy communication strategies and producing a set of recommendations for future research. Key forum conclusions include that communication strategies using personal narratives to engage audiences have the potential to increase public support for policies benefiting those with mental illness or substance use disorders. Specifically, narratives combining personal stories with depictions of structural barriers to mental illness and substance use disorder treatment can increase the public’s willingness to invest in the treatment system without increasing stigma. Depictions of mental illness and violence also increase the public’s willingness to invest in mental health services, but are no more effective than messages about structural barriers to treatment and significantly increase public stigma toward people with mental illness. Future research should prioritize development and evaluation of communication strategies to increase public support for evidence-based substance use disorder policies, including harm reduction-oriented policies such as needle exchange programs and policies expanding treatment.